Antimicrobial Resistance in Swine Fecal Specimens Across Different Farm Management Systems - Pholwat, Suporn; Pongpan, Tawat; Chinli, Rattapha; Rogawski McQuade, Elizabeth T.; Thaipisuttikul, Iyarit; Ratanakorn, Parntep; Liu, Jie; Taniuchi, Mami; Houpt, Eric R.; Foongladda, Suporn (Frontiers in Microbiology, 2020)
Antimicrobial use in agricultural animals is known to be associated with increases in antimicrobial resistance. Most prior studies have utilized culture and susceptibility testing of select organisms to document these phenomena. In this study we aimed to detect 66 antimicrobial resistance (AMR) genes for 10 antimicrobial agent classes directly in swine fecal samples using our previously developed antimicrobial resistance TaqMan array card (AMR-TAC) across 3 different swine farm management systems. This included 38 extensive antimicrobial use (both in treatment and feed), 30 limited antimicrobial use (treatment only), and 30 no antimicrobial use farms. The number of resistance genes detected in extensive antimicrobial use farms was higher than in limited and no antimicrobial use farms (28.2 genes ± 4.2 vs. 24.0 genes ± 4.1 and 22.8 genes ± 3.6, respectively, p < 0.05). A principal component analysis and hierarchical clustering of the AMR gene data showed the extensive use farm samples were disparate from the limited and no antimicrobial use farms. The prevalence of resistance genes in extensive use farms was significantly higher than the other farm categories for 18 resistance genes including blaSHV, blaCTX-M1 group, blaCTX-M9 group, blaVEB, blaCMY2-LAT, aac(6’)-lb-cr, qnrB1, gyrA83L-E.coli, armA, rmtB, aac(3)-IIa, mphA, 23S rRNA 2075G-Campylobacter spp., mcr-1, catA1, floR, dfrA5-14 and dfrA17. These genotypic findings were supported by phenotypic susceptibility results on fecal E. coli isolates. To examine the timing of AMR gene abundance in swine farms, we also performed a longitudinal study in pigs. The results showed that AMR prevalence occurred both early, presumably from mothers, as well as after weaning, presumably from the environment. In summary, detection of AMR genes directly in fecal samples can be used to qualitatively and quantitatively monitor AMR in swine farms.